MOISTURE CURING CONSTRUCTION AND MATERIALS EFFECT - Nabiyev Muminjan (Journals Park Publishing, 2022)
The article studied the effect of moisture on barrier structures and recommended their correct choice. It is illuminated by scientific works on this subject.
Keywords: moisture, condensate, air, structure, aggressive substance, external barrier.